2011
DOI: 10.3390/md9030447
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin: A Potential Therapeutic Agent in Cardiovascular Disease

Abstract: Astaxanthin is a xanthophyll carotenoid present in microalgae, fungi, complex plants, seafood, flamingos and quail. It is an antioxidant with anti-inflammatory properties and as such has potential as a therapeutic agent in atherosclerotic cardiovascular disease. Synthetic forms of astaxanthin have been manufactured. The safety, bioavailability and effects of astaxanthin on oxidative stress and inflammation that have relevance to the pathophysiology of atherosclerotic cardiovascular disease, have been assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(188 citation statements)
references
References 87 publications
5
180
0
3
Order By: Relevance
“…It neutralizes free radicals or other oxidants very efficiently by either accepting or donating electrons without being destroyed or becoming a pro-oxidant in the process. AX predominantly marine origin demonstrated to be a potent antioxidant and anti-inflammatory in several studies (Fassett et al, 2011). The present study showed the improvement of sperm quality during preservation at 5 °C (refrigerator temperature) using TEYCAF extender.…”
Section: Resultssupporting
confidence: 62%
“…It neutralizes free radicals or other oxidants very efficiently by either accepting or donating electrons without being destroyed or becoming a pro-oxidant in the process. AX predominantly marine origin demonstrated to be a potent antioxidant and anti-inflammatory in several studies (Fassett et al, 2011). The present study showed the improvement of sperm quality during preservation at 5 °C (refrigerator temperature) using TEYCAF extender.…”
Section: Resultssupporting
confidence: 62%
“…These functions, together with anti-inflammatory properties, have potential as a therapeutic agent in atherosclerotic disease. Several clinical studies showed favorable data on safety, bioavailability, oxidative stress, and inflammation (24). Furthermore, several animal studies have also shown favorable effects of astaxanthin or synthetic astaxanthin on pathological conditions underlying cardiovascular diseases, namely lowering of blood pressure (25), anti-diabetic effects (26), and attenuation of myocardial infarction size (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin, a keto oxycarotenoid, is a potent antioxidant; its antioxidant activity has been reported to be higher than that of β-carotene, α-carotene, and lutein (Naguib, 2000). Astaxanthin modulates oxidative stress and inflammatory mediators, and has shown to be beneficial against multiple disease models ( Fassett and Coombes, 2011). Astaxanthin inhibited NO production and inflammatory gene expression by suppressing NF-κB activation in lipopolysaccharide-stimulated RAW264.7 macrophage cell lines (Lee et al, 2003).…”
Section: Introductionmentioning
confidence: 99%